Factors Associated With ANC Visits in PHC Hope Raya Pekanbaru 2018: Factors Associated With ANC Visits in PHC Hope Raya Pekanbaru 2018 - Miratu Megasari (Journal of Midwifery and Nursing, 2020)
Visits Antenatal Care (ANC) is suatukegiatan examination conducted by pregnant women to a health professional. From the data obtained by the Health Service coverage pekanbaru 2016 KI KI as many visits as much as 85% and as much as 88.32% K4. While in 2017, PHC Hope Kingdom at coverage increased to 96.0 K1 and K4 visits decreased to 87.1. Antenatal Care service target of Pekanbaru City Health Department for K1 and K4 92.09% 95% The aim of this study was to determine the Factors Associated with ANC Visits in PHC Hope Kingdom Year 2016 type of research is quantitative analytical, design cross sectional. The population in this study all pregnant women who visit antenatal care at the health center Harapan Raya Pekanbaru in January-March 2018, as many as 363 people, while the sample in this study were 78 pregnant women with consecutive sampling technique. The analysis is univariate and bivariate. The results of this study found no relationship between knowledge (p value 0.000 with OR 0.035) attitude (p value 0.000 with OR 3.6) Education (p value 0.006 with OR 0.188) husband support (p value of 0.001 with OR 29.250) and economic status (p value 0,026 with OR 0.172) against ANC visits. The analysis is univariate and bivariate. The results of this study found no relationship between knowledge (p value 0.000 with OR 0.035) attitude (p value 0.000 with OR 3.6) Education (p value 0.006 with OR 0.188) husband support (p value of 0.001 with OR 29.250) and economic status (p value 0,026 with OR 0.172) against ANC visits. The analysis is univariate and bivariate. The results of this study found no relationship between knowledge (p value 0.000 with OR 0.035) attitude (p value 0.000 with OR 3.6) Education (p value 0.006 with OR 0.188) husband support (p value of 0.001 with OR 29.250) and economic status (p value 0,026 with OR 0.172) against ANC visits. It is expected that health practitioners can make home visits and counseling pregnant women about the importance of antenatal care visits for maternal and infant health.